Uporaba šifranta padavinskih območij vodotokov Republike Slovenije za pripravo hidroloških modelov - Šraj, Mojca (Acta hydrotechnica, 2001)
The applicability of the watershed coding system of the Republic of Slovenia is represented in this paper with the emphasis on the hydrological modelling which is the base for flood forecasting, flood risk analyses and precautions against floods, water budget assessments, etc. The hydrological model of the river Soča is represented as an example. The coding system completely tallies with the model-input structure, as can be seen from the example. Therefore the coding system of the Republic of Slovenia enables direct input in the hydrological models.
Keywords: coding system; hidrologija; hydrology; modeliranje; modelling; padavine; padavinsko območje; precipitation; reka Soča; šifrant; the Soča river; watershed